The Determinants Factors of Mobile Payment Adoption in DKI Jakarta - Andre, Grace Violeta; Baptista, Pilander Tias; Setiowati, Rini (Journal of Research in Marketing (ISSN: 2292-9355), 2019)
The escalating growth in the usage of smartphone stimulates business people to innovate with technology, one of the ways is by developing a cashless payment system using cell phones or commonly referred to as mobile payment. Substantial amount of service providers in many countries, particularly Indonesia, has offered mobile payment with various benefits. Hence, this research comprised a study of user behavior towards the implementation of information technology by using a framework model which adopted by using the UTAUT (Unified Theory of Acceptance and Use of Technology) model. To collect the data, questionnaires were distributed through online channels with internet users as potential respondents. This research uses explanatory design with convenience sampling method. Firstly, data were obtained from 30 respondents through online channel and the pre-test result stated that the user interface of mobile payment has a significant effect on the use of MP. From the pre-test result mentioned, questionnaires were redistributed and collected. From this, a total of 220 questionnaires from respondents in DKI Jakarta has been obtained and the majority of respondents have acknowledged the presence of mobile payment. Data processing is conducted by using SmartPLS 3.0 software. This research verified that perceived risk and cost factors are the main disruptions that cause the low adoption rate on the usage of mobile payment in Indonesia, and that social influence has proven to be a highly crucial, driving factor for users in using mobile payment. Word of mouth communication, promotion by Brand Ambassadors and celebrities can be used as recommendations by service providers to formulate better strategies.